Legal liability of nurses in adverse events: A normative-empirical analysis of patient safety governance at RSUD dr. Soeroto Ngawi - Melita Widyastuti; Sri Ayu Astuti; Imam Ropii; Marsudi Dedi Putra; Carolina Kuntardjo (Science Midwifery, 2026)
Adverse events pose a serious threat to patient safety in hospitals. Data from RSUD Dr. Soeroto Ngawi reveal fluctuations in medical incident cases over 2021–2024 (n=354), with procedural and medication errors dominating patient safety reports. A critical research gap persists regarding inconsistent SOP implementation and a blame culture that suppresses transparent incident reporting — gaps unaddressed through an integrated legal-empirical lens. This study aims to analyze forms of nursing negligence, construct a legal accountability framework, and identify barriers and resolution efforts at a regional public hospital. An empirical legal approach was employed, combining case-based and statutory analysis. Data were collected through in-depth interviews with eight key informants, observation, and document review, then analyzed using descriptive qualitative methods with legal triangulation. Results indicate that nursing negligence primarily occurs in patient identification and clinical communication during handover. Nurses' accountability is manifested through immediate clinical responses, IKP system reporting, and root-cause investigations under Law No. 17 of 2023 on Health. Accountability nonetheless remains hindered by psychological barriers and structural workload imbalances. The scientific contribution of this study is the Dual-Layer Accountability Model, which proportionately assigns legal liability between individual professional conduct and institutional systemic failures — a framework absent from prior Indonesian health law scholarship. It is recommended that hospital management adopt a non-punitive just culture, digitize incident reporting, and strengthen clinical risk management training to ensure legal certainty for nurses while advancing patient safety.